Comparison of NEWS, SIRS, and qSOFA Score as Predictors of Mortality and Length of Stay in Patients Pneumonia with Sepsis - Harsini, Harsini; Alfarizi, Aditya; Aphridasari, Jatu; Raharjo, A Farih; Reviono, Reviono (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2024)
Background: Pneumonia is a major health problem in all age groups and often related with sepsis. In 2021, Surviving Sepsis Campaign Guidelines mentioned several clinical scoring systems to identify patients with potentials of developing sepsis, such as systemic inflammatory response syndrome (SIRS), national early warning score (NEWS), quick sequential organ failure assessment (qSOFA) and sequential organ failure assessment (SOFA). The guideline stated that there is no gold standard for diagnosing sepsis, contradicting The Sepsis-3 Guideline in 2016 that mentioned SOFA score as a gold standard for diagnosing sepsis.Methods: Subjects were all patients with pneumonia and sepsis who were treated in Dr.Moewardi Hospital within 1 January to 31 December 2022. Data from subjects’ medical records were collected to assess their NEWS, SIRS, qSOFA, and SOFA score on the day of admission. Since evaluation of SOFA score needs a number of components requiring laboratory results and takes longer time so they made a simpler tool called qSOFA to avoid delayed treatment of the patients.Results: NEWS is more consistent with SOFA compared to SIRS and qSOFA (Kappa value = 0.726 vs 0.320 vs 0.22; respectively). NEWS, SIRS, and qSOFA were all significantly correlated with mortality (P<0.001) with NEWS having the strongest correlation (r=0.482 vs 0.216 vs 0.175; respectively). Only NEWS showed significant correlation with the length of stay (r=0.129; P<0.001).Conclusion: NEWS was the most consistent score to SOFA compared to SIRS and qSOFA. NEWS was also the best predictor for mortality and was the only score correlated with length of hospital stay.